Counseling techniques : a comprehensive resource for Christian counselors - Thomas, John C., 1959- (Grand Rapids, MI. Zondervan Academic, 2018)
Counseling Techniques equips therapists and students with a wide-ranging guide to the fundamental techniques of effective counseling. --
Laying the groundwork / John C. Thomas -- Evidence-based counseling / David Lawson -- Cognitive-based strategies / Gary Sibcy, John C. Thomas -- Emotion-oriented strategies / Todd Bowman -- Emotional dysregulation strategies / Todd Bowman -- Behavioral strategies / John C. Thomas -- Behavioral dysfunction strategies / Stephen P. Greggo -- Experiential strategies / John C. Thomas -- Spiritual strategies / Fernando Garzon -- Christian formation of the self strategies / Ian F. Jones -- Coping skills strategies / Amanda M. Blackburn, E. Nicole Saylor -- Attachment-oriented strategies / Gary Sibcy -- Child-focused strategies / Kevin B. Hull -- Adolescent-focused strategies / Andi J. Thacker -- Couple-focused strategies / Fredrick A. DiBlasio -- Family-focused strategies / Fredrick A. DiBlasio, Amanda G. Turnquist -- Family of origin-focused strategies / Fredrick A. DiBlasio -- Family conflict-focused strategies / Linda Mintle -- Domestic violence-focused strategies / Lynne M. Baker -- Forgiveness-focused strategies: the REACH forgiveness model / Everett L. Worthington Jr., Steven J. Sandage, Jennifer S. Ripley -- Shame-focused strategies / John C. Thomas -- Trauma-focused strategies / Heather Davediuk Gingrich -- Nonsuicidal self-injury-focused strategies / David Lawson -- Loss-focused strategies / Eric Scalise -- Sexual addiction-focused strategies / Mark R. Laaser -- Infidelity-focused strategies / Michael Sytsma, Douglas Rosenau -- Betrayed spouse-focused strategies / Debra Laaser -- Couple sexual problems-focused strategies / Michael Sytsma.
Includes bibliographical references and indexes.
Keywords: Counseling -- Religious aspects -- Christianity; Counselors -- Training of